Positioning Control Performances Of A Robotic Hand System - Mohamad Yuden, Mohamad Adzeem; Md Ghazaly, Mariam; Che Amran, Aliza; Jamaludin, Irma Wani; Khoo, Hui Yee; Yaacob, Mohd Rusdy; Abdullah, Zulkeflee; Yeo, Chin Kiat (UTM Press, 2017)
Hazardous environments such as in industry sector with high chemical usage give high risks to the safety of workers. These risks can be reduced by designing robotic hand that is able to replace human works. For the industry purpose, the robotic hand needs to have a higher performance in accuracy, stability and consistency. However, the current robotic hand in industry is not flexible, which means it cannot be used for different tasks. Therefore, a multi-purpose robotic hand was developed. In this paper, the objectives of this research are to design and develop a PID controller for improving the performances of a robotic hand system. The experimental results prove that the PID controller shows good performances with the steady state error less than 0.110 for the input reference, 300 respectively.